Carbon nanotubes and nanoparticles : current and potential applications - Vakhrushev, Alexander V.; Kodolov, Vladimir I. (Vladimir Ivanovich); Haghi, A. K.; Ameta, Suresh C. (Toronto ; New Jersey : Apple Academic Press, 2019)
This new volume looks at significant new research, methodologies, and applications in the fields of carbon nanotubes and nanoparticles. It explores a variety of new developments in advanced carbon nanotubes and nanoparticles along with the tools to characterize and predict their properties and behavior. It introduces and reviews methods that are most frequently encountered in sophisticated nano-scaled materials domains,and helps to bridge the gap between classical analysis and modern real-life applications. A diverse array of topics in the field is addressed that provides many practical insights into nanocomposites and nanomaterials sciences.
Carbon nanotube as versatile carrier in drug delivery / C.K. Sudhakar, Nitish Upadhyay, Sanjay Jain, and R. Narayana Charyulu -- A review on computational study of carbon nanotubes / Hiteshi Tandon, Shalini, Prabhat Ranjan, Vandana Suhag, and Tanmoy Chakraborty -- Carbon nanotube composites as photocatalytic materials / Rakshit Ameta, Neha Kapoor , Bhavya Pathak, Jayesh Bhatt, and Suresh C. Ameta -- Adsorption of cholesterol by carbon nanotubes / Alexander V. Vakhrushev, A.A. Vakhrushev, N.N. Chuckova, I.A. Cherenkov, and N.V. Cormilina -- Carbon nanotubes : a concise review of the synthesis techniques, properties, and applications / Saumya Shalu, Kakoli Dasgupta, Anuradha Kumari, and Barnali Dasgupta Ghosh -- Conducting polymer/CNT-based nanocomposites as smart emerging materials / Neha Kanwar Rawat, P.K. Panda, and Anujit Ghosal -- Carbon nanotubes and their applications in chemical engineering science : a far-reaching review / Sukanchan Palit -- The hydrogen batteries based on carbon nanotubes / I.A. Shestakov, S. S. Vidrina, and Alexander V. Vakhrushev -- Carbon nanotubes and material science: a critical overview and a vision for the future / Sukanchan Palit -- Carbon nanotubes : properties and applications / Sonia Khanna -- Change in the electronic structure and magnetic properties of modified copper/carbon nanocomposites / V.I. Kodolov, V.V. Trineeva, N.S. Terebova, I.N. Shabanova, T.M. Makhneva, R.V. Mustakimov, and A.A. Kopylova -- Mechanochemical modification of metal/carbon nanocomposites / V.I. Kodolov, V.V. Trineeva, A.A. Kopylova, R.V. Mustakimov, S.A. Pigalev, N.S. Terebova, T.M. Makhneva, and I.N. Shabanova -- Self-nanoemulsifying drug delivery system: formulation development and quality attributes / Pankaj V. Dangre and Shailesh S. Chalikwar -- The investigation of copper/carbon nanocomposite aqueous sols for application at the cultivation of lilies / A.A. Lapin, V.M. Merzljakova, and V.I. Kodolov -- Metal/carbon nanocomposites and modified analogous: possible participation in vital processes / V.I. Kodolov, V.V. Trineeva, A.A. Lapin, and V.M. Merzljakova.
OCLC-licensed vendor bibliographic record.
Keywords: Carbon nanotubes; Nanoparticles; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; SCIENCE / General; TECHNOLOGY / Material Science; TECHNOLOGY / Nanotechnology